Age-Related Changes in Human Schlemm’s Canal: An in Vivo Optical Coherence Tomography-Based Study - Zhao, Yujin; Chen, Junyi; Yu, Xiaobo; Xu, Jianjiang; Sun, Xinghuai; Hong, Jiaxu (Frontiers in Physiology, 2018)
Purpose: To investigate age-related changes in human Schlemm’s canal (SC) using spectral-domain optical coherence tomography (SD-OCT). Methods: A total of 125 normal eyes were imaged using SD-OCT nasally and temporally. The age-related variations of SC sagittal diameter and cross-sectional area (CSA) from four age groups [A (16–20 years), B (21–40 years), C (41–60 years), and D (61–80 years)] were analyzed with Spearman correlation. Results: The positive detection rates of SC showed a significantly downward trend with age. The mean CSA was 13,296 ± 1,897 μm2 nasally and 14,552 ± 2,589 μm2 temporally. The mean CSA was significantly larger in the temporal than in the nasal region (P < 0.05). Nasal CSA values varied among the four age groups (P = 0.004). Conclusions: Our study found for the first time that SC in vivo exhibits a morphological variant with age in healthy humans. Clinicians may need to consider this phenomenon when performing examinations targeting SC for glaucoma patients.